FORMULATION AND EVALUATION OF COMBINATION TABLETS AMLODIPINE BEYSILATE AND POTASSIUM LOSARTAN - Pratama Putra, Gilang
Amlodipine besylate (AMB) is a drug of the Calcium Channel Blocker (CCB) class dihydropyridine and potassium losartan (LSK) an angiotensin II receptor antagonist. The combination two drugs provides a synergistic effect treatment of hypertension. The purpose of this study was to formulate a combination of AMB and LSK tablets compared to innovator tablets. The formulation of combination tablets was first carried out by developing of each formula tablet the similarity (f2) above 50, then developed into a combination tablet of AMB and LSK. The additional ingredients used are amylum, mucilago amili, PVP K30, SSG, Avicel pH 101, Collidon CL-M, calcium carbonate, calcium dihydrogen phosphate, talc, and magnesium stearate. The tablets obtained were then evaluated, especially the speed of the dissolution on three different pH mediums, namely pH 1.2, pH 4.5 and pH 6.8. The AMB (F4) tablet formula containing PVP K30, SSG, Avicel pH 101, talcum, and magnesium stearate provides a similarity value (f2) above 50 while the LSK (F4) tablet formula containing PVP K30, SSG, Avicel pH 101, Collidon CL- M, talcum, and magnesium stearate provides a similarity value (f2) above 50. The results of the dissolution of the combination of AMB and LSK tablets from the combined formula more than provide similarity values (f2) to innovator tablets in medium with pH 1.2 are 50.78 (AMB) and 50.08 (LSK), in medium with pH 4.5 are 50.77 (AMB) and 50.14 (LSK), in medium with pH 6.8 are 50.13 (AMB) and 50.35 (LSK). The combination tablet formula provides a similarity value (f2) above 50 on all three different pH mediums.